Síntese de nanoadsorventes e chars a partir da pirólise de bagaço de uva para fins de adsorção - Silva, Caroline Machado Sebem da (2022)
Graphene has received great attention due to its excellent properties. Commonly, its synthesis is carried out from graphite. However, because graphite is a non-renewable material, it is necessary to develop graphene synthesis routes from others precursors. In this sense, graphene-like materials have been synthesized/studied. Among the possible precursors, agricultural residues, called biomass, stand out, which are a great alternative for the synthesis of various materials. Between the biomasses, the grape bagasse stands out due to the large quantities which is generated, mainly by the activities of viticulture. The use of thermochemical conversion processes, such as pyrolysis, is one of the alternatives used in the recovery of these wastes, resulting in products with greater added value. In this work, six adsorbents materials were produced from grape bagasse through pyrolysis. Grape bagasse was initially characterized in order to verify its possible use in pyrolysis processes to obtain adsorbent materials. First, three chars (C700, C800 and C900) were produced at different pyrolysis temperatures (700, 800 and 900 ºC). These chars were characterized according to their chemical and textural properties, and, later used in the study of adsorption of copper ions (Cu(II)) from aqueous solutions. The chars showed different textural characteristics, but similar chemical surfaces and Cu(II) adsorption potential. The char produced at 700 ºC (C700) showed better performance in the adsorption study, with a maximum adsorption capacity of 42 mg g-1 . In a second step, three nanoadsorbents materials were produced at the same pyrolysis temperatures, called graphene-like porous carbon nanosheets (GPCN700, GPCN800 and GPCN900). These nanoadsorbents were characterized and their results were compared to the chars. The six materials (chars and nanoadsorbents) were used in the adsorption of carbon dioxide gas (CO2(g)). The GPCNs presented specific surface areas notably larger than the chars, and the GPCN900 presented the largest area found (1062.696 m2 g -1 ). While the chars were classified as mesoporous, the GPCNs showed micropores, which resulted in higher CO2(g) adsorption capacities (168.71 mg CO2(g) g -1 ).